Dukungan Keluarga dan Gangguan Pemenuhan ADL dengan Respon Emosional pada Pasien Pasca Stroke Iskemik - Mahardika, Norma Yulianti; Susilo, Rakhmat; Asiandi, Asiandi; Supriyadi, Supriyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the relationship between family support and impaired fulfillment of ADL with emotional responses in post-ischemic stroke patients at the Neurology Clinic of Prof. Dr. Margono Soekarjo Hospital, Purwokerto. The method used is quantitative with a cross-sectional approach. The results of the study showed that 60 respondents had characteristic results in the gender category, the most in the male gender, as many as 35 respondents (58.3%) and the most age category at the age of >50 years, as many as 47 respondents (78.3%), post-stroke patients suffered the most extended stroke at a time of >6 months as many as 44 respondents (73.3%). The statistical test results showed (p-value 0.001 = <0.05) ischemic. In conclusion, there is a relationship between family support and impaired fulfillment of ADL with emotional responses in post-ischemic stroke patients at the Neurology Clinic of Prof. Dr. Margono Soekarjo Hospital, Purwokerto. Keywords: Family Support, Impaired Fulfillment of ADL, Emotional Response, Ischemic Stroke